From Theory to Practice: Enhancing Translation Skills through Syntax Mapping and Shift Strategies - Chairina, Melyanda Agustin; Febriansyah, Gema; Yudistira, Sukma; Fajardo, Dan Fareth; Elvonny, Tia Kharina (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2025)
This study explored the integration of syntax mapping and shift strategy instruction to enhance translation competence in vocational education. Framed within a Design-Based Research (DBR) approach, the study addressed common challenges among novice translators, including literal translation tendencies, syntactic rigidity, and low awareness of pragmatic shifts. Conducted in an Indonesian polytechnic with 25 students, the intervention followed four DBR phases: needs analysis, tool design, implementation, and evaluation. Data were collected through pre- and post-tests, worksheet tasks, and student reflections. Descriptive results indicated improvement in translation test scores (from 64.3 to 78.4) and syntax mapping accuracy (from 62.3% to 76.0%), along with increased application of lexical, class, and structural shifts. Student reflections revealed enhanced metacognitive awareness and more analytical decision making. However, the study did not include hypothesis testing or inferential statistics; therefore, claims regarding the tool’s effectiveness are based on observed descriptive gains and should be interpreted with caution. Additionally, the small sample size and specific vocational context limit generalizability. Future studies should incorporate statistical analyses and broader samples to validate the impact and explore applicability across different educational contexts and language pairs.